(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: The integration of Artificial intelligence (AI) into various sectors, including transportation, has a significant impact on human endeavors, in addition to eco-friendly advantages. One of the most promising areas of AI-powered systems is the manufacture of Autonomous Vehicles (AVs). These self-driving cars, also known as driverless, are intelligent vehicles that can operate without human aid or support. AVs are equipped with sophisticated AI-powered technologies such as sensors, radars, Global Positioning System (GPS), and advanced algorithms that can transmit information and navigate the environment using analyzed data. These driverless cars have the potential of revolutionizing the transport sector by improving efficiency, reducing road accidents, improving flexibility, and decreasing congestion. However, AI in AV applications poses some risks and challenges associated with securing systems from cybersecurity threats and attacks. This paper explores the dangers and difficulties of securing AI systems from cyber threats, highlighting various detection and prevention mechanisms. The ethical and legal implications, including strategies to address these challenges proactively, are also discussed. It is believed that the challenges in the automotive industry can be mitigated through collaboration among stakeholders, manufacturers, researchers, IT professionals, and policymakers by implementing robust security measures, conducting regular vulnerability assessments, and leveraging the expertise of software security specialists. Collaboration between industry and cybersecurity professionals is essential to safeguarding public safety.